(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Surrogate mothers’ account production of pregnancy misfortune on surrogacy support sites is being explored by scientists. Women create the public online world of surrogacy by communicating through the Internet. I investigate the connections between conceptualizations of misfortune and understandings of innovative practices, as well as the ramifications of these understandings for helped proliferation, utilizing anthropological and humanistic literatures. Surrogate mothers define losses as the failure to implement a child to the intended parents that might include anything from infertility to miscarriages as well as stillbirth. By increasing expectations of success, trying to optimize outcomes via the relocation of several impregnated eggs, as well as conducting initial monitoring and analyzing, assisted the reproductive technologies which lead to loss. Surrogates, on the other hand, see technology as a good factor and support reproductive technology. Surrogates’ fortitude to "give the gift of life" leaves them susceptible to failures as well as losses, but it also motivates them to try again and again to carry children for others using technology.